Barriers and enablers to adoption and diffusion of eLearning: A systematic review of the literature – a need for an integrative approach. Issue 2 (8th April 2014) - Singh, Gurmak; Hardaker, Glenn
Abstract : Purpose: – The purpose of this paper is to identify and examine the antecedents that enable or constrain the adoption and diffusion of eLearning in higher education (HE). The key focus of the study is on the examination of how the organisation's diffusion structures, systems or processes influence the individual adoption of eLearning. The findings from this literature review contribute to practice through providing a better understanding of the issues associated with institutional diffusion mechanisms that aid the adoption of learning technologies. Design/methodology/approach: – An extensive search of the literature was conducted. The selected references were analysed into a number of categories; macro-level studies examining HE context of eLearning, micro-level studies focusing on individual and social factors and articles focusing on management issues of adoption and diffusion of technological innovations. Finally, over 300 articles were used to compile the findings of this paper. Findings: – The paper argues that future research studies should not model the adoption and diffusion of eLearning based primarily on either an individualist (Micro) or structuralist (Macro) perspective, but by using a more interactive approach to examine the complexity and multiple levels and dimensions of social reality. Research limitations/implications: – A significant exclusion and one which clearly calls for further research, is the aspect of institutional structures such as library systems, virtual learning environments, administrative support systems and other technical systems such as enrolment, registration, assessment and students, with respect to the adoption of eLearning. Future studies may want to explore the interplay between these structures and agency. Practical implications: – The study findings contribute to practice through providing a better understanding of the issues associated with institutional diffusion mechanisms that aid the adoption of learning technologies. Considering the slow and often disappointing adoption of eLearning within higher education institutions (HEIs), the study reveals the nature of adoption that may inform the development of institutional eLearning diffusion structures. Social implications: – The paper identifies that the importance of individual factors influencing the adoption of eLearning has been acknowledged by the above studies, and the underlying message has emerged that levels of eLearning adoption would be higher if strategic managers recognised the social dimensions of eLearning innovation and diffusion, such as: academic and professional goals, interests and needs; technology interests; patterns of work; sources of support; and social networks. The argument is that currently eLearning is geared towards technically "literate" and innovative staff, and this strategy reduces the likelihood of mainstream faculty actually adopting instructional technology for their own teaching. Originality/value: – A review of the eLearning literature shows that there only a few substantive theoretical accounts which adequately integrate multiple levels of analysis and explain adoption and diffusion of eLearning in terms of the interplay between structural influences and individual action. The paper argues for future research to be integrated in a general analytical framework.